Lokalni izbori - nacionalne teme: Centralizujuća personalizacija lokalnih izbora u Srbiji - Bogićević, Katarina (Politički život, 2025)
The 2024 local elections in Serbia are characterized by a campaign in which national themes predominantly occupied a central place while the questions and issues relevant to specific local communities were marginalized. This paper explores various determinants that shape national-oriented campaigns and their impact on voter behavior, with the emphasis on persuasive techniques used in media and mobilization of public resources by the ruling party. The study aims to comprehend the roots of the nationalization process of local elections and the crucial implications on democratic process. Using the method of critical discourse analysis (CDA) of media coverage (electronic media with national coverage, mainstream printed media and digital editions, as well as prominent local media), the paper offers comprehensive insights in the campaign strategies and their effectiveness.